Drug addiction and families - Barnard, Marina (Kingsley, 2007)
What is the problem? -- Family journeys of discovery, adaptation and expulsion : cycles of response to drugs in the family -- Distorted roles and strained relationships -- Practitioner responses to mothers and fathers, brothers and sisters of problem drug users -- Parenting in the midst of a drug problem -- Children growing up with parents who have drug problems -- Stepping into the breach : when the extended family takes on the care of children -- Proliferating problems : exposure to drugs and drug initiation -- Practitioner responses to drugs in the home -- Conclusion : what needs to happen? A case of tinkering or overhaul?